Evaluation of antibody responses of cattle and buffaloes to Clostridium perfringens type A vaccine using ELISA - Lily Natalia (Jurnal Ilmu Ternak dan Veteriner, 1995)
An enzyme-linked immunosorbent assay (ELISA) was developed to detect specific antitoxin Clostridium perfringens type A. It was based on the use of purified alpha toxin of Clostridium perfringens type A as the coating antigen, which was then linked to specific alpha antitoxin . Horse raddish peroxidase labelled IgG was used as the conjugate, and 2,2-azino-bis (3- ethylbenzthiazoline-6-sulfonic acid) (ABTS) as the substrate . The ELISA was used to evaluate vaccination results on cattle and buffaloes against enterotoxaemia caused by Clostridium perfringens type A.